PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN MATHEMATICS IN CONTEXT PADA KEMAMPUAN DAN KETERAMPILAN BERPIKIR KREATIF - Eka Farida Fasha (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractÂ The purpose of this study is to determine the increase of creative thinking ability and creative thinking skill in mathematics learning with mathematic in context approach. The technique analisys used is the average comparative test for pretest and posstest data. To see an increased creative thinking skill, researcher compare the average value of creative thinking skills from the first meeting, the meeting II and III meeting. The result showed that there is an increasing of creative thinking ability and crtative thinking skill in mathematics learning with mathematic in context approach.